The Policy Implementation of The Tax Regional Optimalization in The City Kediri (Case Study in the Local Office of Revenue, Finance Management and Asset in The City of Kediri) - Tari, Novi Rilin (Jurnal Administrasi Publik, 2013)
Abstract: The Policy Implementation of The Tax Regional Optimalization in The City Kediri (Case Study in the Local Office of Revenue, Finance Management and Asset in The City of Kediri). Tax is an important source of revenue for the state treasury because taxes are a source of funding that can not be compromised and it is the requirement for every citizen to fulfill it. These needs include for public facilities and financing viability of the state. All in all, this scenario will ultimately lead in to one goal which is improving better welfare of the community. Therefore, taxation is indeed, need good mechanism to improve taxpayer compliance. The kind of study use descriptive method with qualitative approach. The focuses of this studies are The effort taken by the Department of Revenue, Finance Management and Asset Kediri to increase the obedient of Taxpayer, The descriptions of taxpayers compliance in paying local taxes are, The supporting and constrainingfactors in payments or delays of local taxes in Kediri which are balancing the correlation between the taxpayers and the Department of Revenue, Finance Management and Asset Kediri. Data analysis which is conducted by the research is the analysis of an interactive model developed by Miles and Huberman. Implementation by the law major regulation in Kediri no. 6 year 2010 about local tax have a good execute, this can see from accuracy paymant by taxpayers. Almost of tax implementation appropriate target, then the local revenue of tax year by year increas. Recommendations offered to the problems included the self-assessment system improvement and the socialization of new type of tax requiring the compliance of new payment provisions.  Human resources whose skills and competence fit the field would boost the performance of Department of Revenue, Finance Management and Asset Kediri. Keyword: implementation policy, local taxation, local revenue.   Abstrak: Implementasi Kebijakan Optimalisasi Pajak Daerah di Kota Kediri (Studi Kasus pada Dinas Pendapatan, Pengelolaan Keuangan dan Aset). Pajak merupakan sumber penerimaan yang penting bagi kas negara, karena pajak merupakan sumber pembiayaan yang tidak dapat ditawar lagi atau disebut dengan kewajiban. Kebutuhan tersebut mencakup fasilitas publik dan pembiayaan kelangsungan hidup negara. Dimana kebutuhan tersebut  mengarah pada satu tujuan yaitu, meningkatkan kesejahteraan masyarakat menjadi lebih baik. Peneliti menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif. Upaya yang ditempuh oleh Kantor Pelayanan Pajak Kota Kediri untuk meningkatkan kepatuhan Wajiib Pajak. Gambaran/ deskripsi kepatuhan Wajib Pajak dalam membayar pajak daerah.Apakah faktor penghambat dan pendorong dalam pelaksanaan pembayaran atau penundaan Wajib pajak pajak daerah di Kota Kediri sehingga terjadi korelasi yang seimbang antara Wajib Pajak dan Kantor Pelayanan Pajak. Analisis data yang dilakukan oleh penelitian adalah analisis dari sebuah model interaktif yang dikembangkan oleh Miles Dan Huberman. Implementasi peraturan walikota Kediri no. 6 tahun 2010 tentang pajak daerah dilaksanakan dengan baik, hal ini dapat dilihat dari ketepatan pembayaran yang dilakukan oleh wajib pajak. Sebagian besar pajak direalisasikan sesuai target awal yang sudah ditentukan, kemudian pendapat pajak setiap tahunnya mengalami kenaikan.  Rekomendasi terhadap permasalahan yang timbul meliputi mengimprove kembali sistem self-assessment dan mensosialisikan jenis pajak baru agar wajib pajak patuh terhadap ketentuan pembayaran pajak baru. Sumber daya manusia yang terampilan dan kompetensi sesuai bidang akan meningkatkan kinerja Dinas Pendapatan, Pengelolaan Keuangan dan Aset Kediri. Kata Kunci: implementasi kebijakan, pajak daerah, pendapatan daerah.